2015
DOI: 10.1155/2015/761718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Atmospheric Pressure Plasma Treatment for Implant Osseointegration

Abstract: This study assessed the osseointegrative effects of atmospheric pressure plasma (APP) surface treatment for implants in a canine model. Control surfaces were untreated textured titanium (Ti) and calcium phosphate (CaP). Experimental surfaces were their 80-second air-based APP-treated counterparts. Physicochemical characterization was performed to assess topography, surface energy, and chemical composition. One implant from each control and experimental group (four in total) was placed in one radius of each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
2
32
1
1
Order By: Relevance
“…The surface roughness of the implant was recognized as the most important determent of the osseointegration of the dental implants Increased surface roughness has enhanced the osteoblast differentiation and local factor production in vitro, as well as bone-toimplant contact and torque removal forces in vivo (44) In the present study, Energy-dispersive x-ray spectroscopy showed statistically significant increase in both Ca, Al and Si in the atmospheric pressure plasma treated CFR-PEEK implant surface The highest increase was in the silica particles This in agreement with results Noeske et al (43) that showed that the surface of polymers after plasma treatment increased the percent of Si, Ca and oxygen Moreover, Danna et al (41) confirmed the same results in their study of atmospheric pressure plasma treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The surface roughness of the implant was recognized as the most important determent of the osseointegration of the dental implants Increased surface roughness has enhanced the osteoblast differentiation and local factor production in vitro, as well as bone-toimplant contact and torque removal forces in vivo (44) In the present study, Energy-dispersive x-ray spectroscopy showed statistically significant increase in both Ca, Al and Si in the atmospheric pressure plasma treated CFR-PEEK implant surface The highest increase was in the silica particles This in agreement with results Noeske et al (43) that showed that the surface of polymers after plasma treatment increased the percent of Si, Ca and oxygen Moreover, Danna et al (41) confirmed the same results in their study of atmospheric pressure plasma treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Although a time‐dependent increase in hydrophilicity was shown by Aita et al . for UV light up to 48 h of treatment , a time interval above 15 min seems to be barely practicable under clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the effects of UV light and non‐thermal plasma on titanium and zirconia surfaces in changing the surface chemistry, attracting cells in vitro, and finally improving osseointegration in vivo (, , ). Apart from examining superhydrophilicity, Noro et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma medicine applications include treatment of oral biofilm-related infections [12,13], treatment of wounds and skin diseases [19][20][21], assistance in cancer treatment [22][23][24], treatment of viruses infections (e.g. herpes simplex [25]); as well as, but not limited to, optimization of implants surfaces [26][27][28]. Each of those applications will be discussed in this review article ( Fig.…”
Section: Introductionmentioning
confidence: 99%